From Activism to Radicalization: The Evolution of Vaccine Disinformation in the Brazilian Social Media Ecosystem (2021–2025) - Chinazzo, Luana; Teixeira de Oliveira, Anna Julia; Bragança, Lucas; Firme, Julia; Goveia, Fabio; Sodré, Francis (Revista Española de Comunicación en Salud, 2026)
Introduction: This article analyzes the evolution of the vaccination discourse in Brazil on the X platform, comparing the civic mobilization of 2021 with the radicalization and collapse of dialogue observed in 2025. Objectives: To analyse “Platform Effect” as the central variable explaining the discursive shift over time. Methodology: A comparative-longitudinal approach was used, employing semantic network analysis and co-occurrence graphs to map narratives and ecosystems across both periods. Results: Findings indicate that in 2021, platform architecture reduced organizing costs (Shirky), facilitating pro-vaccine activism. In contrast, 2025 shows the consolidation of radical niches where disinformation is quantifiably relevant, attributed to the reversal of affordances. The algorithmic prioritization of conflict and emotional intensity elevated contestation costs for scientific voices (Gillespie), creating a discursive vacuum. The anti-vaccine discourse became a “cultural war” against the PNI. Conclusion: The fight against disinformation is inseparable from the debate on the regulation and design of digital architecture, given the severe threat to public health and democratic integrity.